2015
DOI: 10.1371/journal.pone.0117809
|View full text |Cite
|
Sign up to set email alerts
|

miR-101 Suppresses Vascular Endothelial Growth Factor C That Inhibits Migration and Invasion and Enhances Cisplatin Chemosensitivity of Bladder Cancer Cells

Abstract: BackgroundThe microRNA miR-101 is downregulated in several cancers, including bladder cancer. However, miR-101’s role in the invasion, metastasis, and chemosensitivity of bladder cancer cells remains unclear. This study was conducted to determine miR-101’s role on the lymphangiogenic molecule vascular endothelial growth factor C (VEGF-C) and their effects upon bladder cancer cell migration, invasion, and chemosensitivity to cisplatin.MethodsTwo bladder cancer cell lines (T24 and 5637) and the tool cell line 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Zhang et al (7) found that reduced miR-101 expression in bladder transitional cell carcinoma (BTCC) is associated with poor prognosis. Several targets of miR-101 have been identified in bladder cancer, including c-Met, cyclooxygenase (COX)-2 and vascular endothelial growth factor (VEGF)-C (8)(9)(10). However, the underlying mechanisms of the regulatory effects of miR-101 on bladder cancer cell proliferation and invasion have remained largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (7) found that reduced miR-101 expression in bladder transitional cell carcinoma (BTCC) is associated with poor prognosis. Several targets of miR-101 have been identified in bladder cancer, including c-Met, cyclooxygenase (COX)-2 and vascular endothelial growth factor (VEGF)-C (8)(9)(10). However, the underlying mechanisms of the regulatory effects of miR-101 on bladder cancer cell proliferation and invasion have remained largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression of miR-101 in patients with NSCLC has been shown to be related to reduced overall survival [25] through the promotion of cell proliferation, tumorigenesis, and invasion. Previous studies have indicated that low miR-101 expression contributes to chemotherapy-resistance in epithelial ovarian cancer [26], bladder cancer [27] and lung cancer [16]. However, whether miR-101 plays an important role in chemotherapy-induced EMT is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of miR-101 has previously been observed in various human cancers, such as gastric cancer (18), hepatocellular carcinoma (19), nasopharyngeal carcinoma (20), osteosarcoma (21), and breast cancer (22). Furthermore, miR-101 has been identified as a tumour suppressor in bladder cancer (23,24). Downregulation of miR-101 is associated with poor prognosis of patients with bladder transitional cell carcinoma (24).…”
Section: Introductionmentioning
confidence: 98%
“…Downregulation of miR-101 is associated with poor prognosis of patients with bladder transitional cell carcinoma (24). miR-101 directly targets vascular endothelial growth factor C, inhibits cell migration and invasion, and enhances cisplatin sensitivity by modulating the cyclooxygenase-2 pathway in bladder cancer cells (23,25). Our previous study illustrated that miR-101…”
Section: Introductionmentioning
confidence: 98%